Working-class women's experiences of higher education in post-war Britain - White, BA (2019)
This thesis is the first focused study of working-class women who attended higher education institutions in England and Wales in the 1960s and 1970s. A very small proportion of working- class women completed courses of higher education in this period, despite educational reforms such as the Education Act of 1944 and the Robbins Report of 1963. As a result, historical studies of working-class women in the post-war period have not focused on those who pursued higher education, while studies of higher education rarely pay attention to the experiences of working-class women. By analysing thirty-seven oral history interviews, together with published statistics, written reminiscences, and contemporary social surveys, this thesis explores the impact of higher education on the lives of working-class women who matriculated between 1965 and 1975. By taking a life history approach, it analyses the place of higher education in women’s life trajectories, rather than focusing on the experience of higher education alone. The thesis explores, in turn, how women came to apply to higher education; women’s experiences of higher education; and women’s post-graduate careers and social mobility. By exploring experiences at colleges of higher education as well as universities, this thesis offers the first insights into differences between types of institution for working-class women students. At the same time, this thesis considers whether and why these women had a distinctive generational experience. This thesis argues that higher education had a significant impact on these working-class women’s lives, by facilitating social and occupational mobility and influencing women’s senses of class and generation. Crucially, this impact was facilitated by the post-war social and economic context, particularly the introduction of mandatory student grants in 1962. However, this thesis also contends that this was not a golden age of social mobility through education. Thus, this period was one of both unprecedented opportunities and continuing limitations.